IL 33 Correlates With COVID-19 Severity, Radiographic and Clinical Finding - Markovic, Sofija Sekulic; Jovanovic, Marina; Gajovic, Nevena; Jurisevic, Milena; Arsenijevic, Nebojsa; Jovanovic, Marina; Jovanovic, Milan; Mijailovic, Zeljko; Lukic, Snezana; Zornic, Nenad; Vukicevic, Vladimir; Stojanovic, Jasmina; et al. (Frontiers in Medicine, 2021)
Objective: Increased level of IL-33 is considered as a predictor of severe COVID-19 infection, but it’s role at different stages of disease is still unclear. Our goal was to analyze the correlation of IL-33 and other innate immunity cytokines with disease severity. Methods: In this study, 220 COVID-19 patients were included and divided into the two groups, mild/moderate and severe/critical. Value of cytokines, clinical, biochemical, radiographic data were collected and their correlation with disease severity was analyzed. Results: Most patients in the severe/critical group were male (81.8%) and older (over 64,5 years). We found statistically significant difference (p < 0.05) in these two groups between clinical features (dyspnea, dry cough, fatigue, auscultatory findings); laboratory [(neutrophil count, lymphocyte count, monocyte count, hemoglobin, plasma glucose, urea, creatinine, total bilirubin (TBIL), direct bilirubin (DBIL), aspartate aminotransferase (AST), albumin (ALB), lactate dehydrogenase (LDH), creatinine kinase (CK), D-dimer, C-reactive protein (CRP), procalcitonin (PCT), Fe, Ferritin)], arterial blood gases (oxygen saturation-Sa02, partial pressure of oxygen -p02), Chest X-rays (CXR) lung findings (p = 0.000). We found a significantly higher serum concentration (p < 0.05) of TNF-α, IL-1β, IL-6, IL-12, IL-23 and IL-33 in COVID-19 patients with severe disease. In the milder stage of COVID-19 positive correlation was detected between IL-33 and IL-1β, IL-12 and IL-23, while stronger positive correlation between serum values of IL-33 and TNF-α, IL-1β, IL-6, IL-12 and IL-23 was detected in COVID-19 patients with severe disease. Weak negative correlation (p < 0.05) between pO2 and serum IL-1β, IL-12 and IL-33 and between SaO2 and serum IL-33 was noted. Positive relation (p < 0.05) between serum values of IL-33 and IL-12, IL-33 and IL-6 and IL-6 and IL-12 is proven. Conclusion: In a more progressive stage of COVID-19 increased IL-33 facilitates lung inflammation by inducing the production of various innate proinflammatory cytokines (IL-1β, IL-6, TNF-α, IL-12, IL-23) in several target cells leading to the most severe forms of the disease. IL-33 correlates with clinical parameters of COVID-19 and might represent a promising marker as well as a therapeutic target in COVID-19.